2021
DOI: 10.1038/s41467-021-25736-8
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically disordered protein biosensor tracks the physical-chemical effects of osmotic stress on cells

Abstract: Cell homeostasis is perturbed when dramatic shifts in the external environment cause the physical-chemical properties inside the cell to change. Experimental approaches for dynamically monitoring these intracellular effects are currently lacking. Here, we leverage the environmental sensitivity and structural plasticity of intrinsically disordered protein regions (IDRs) to develop a FRET biosensor capable of monitoring rapid intracellular changes caused by osmotic stress. The biosensor, named SED1, utilizes the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 53 publications
(60 reference statements)
0
46
0
Order By: Relevance
“…Precedent for switch-like transitions and dynamics that span a spectrum of timescales has been reported for different IDRs ( 10 , 13 ). Such transitions, especially in the context of tethered systems, are likely to make important contributions to the spatial and temporal control over biochemical reactions where IDRs modulate the effective concentrations of ligands around binding sites or of substrates around active sites of enzymes ( 31 , 32 , 34 , 57 , 101 105 ). While our results are presented for IDRs studied as autonomous units, we expect that our findings will be transferable to tethered IDRs, albeit with context-dependent modifications ( 103 , 106 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precedent for switch-like transitions and dynamics that span a spectrum of timescales has been reported for different IDRs ( 10 , 13 ). Such transitions, especially in the context of tethered systems, are likely to make important contributions to the spatial and temporal control over biochemical reactions where IDRs modulate the effective concentrations of ligands around binding sites or of substrates around active sites of enzymes ( 31 , 32 , 34 , 57 , 101 105 ). While our results are presented for IDRs studied as autonomous units, we expect that our findings will be transferable to tethered IDRs, albeit with context-dependent modifications ( 103 , 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies over the past decade have helped quantify relationships ( 6 ) that connect sequence-encoded information within IDRs to properties of conformational ensembles such as overall sizes and shapes, the amplitudes of spontaneous conformational fluctuations, and the dynamics of interconverting between distinct conformational states ( 7 19 ). These sequence–ensemble relationships have direct functional consequences that have been uncovered via studies based on biophysical, biochemical, and engineering approaches ( 5 , 20 38 ). Our work, which is focused on physical principles underlying sequence–ensemble relationships of IDRs, is of direct relevance to understanding how IDRs function.…”
mentioning
confidence: 99%
“…We further observed that during imaging, “SFH8 IDR ” puncta lacked colocalization with vesicular markers ( Figure S4F, G ), and showed LLPS hallmarks such as dynamic morphology with frequent splitting, fusion, and interconnections ( Movie S4, Figure S4H ). FRAP of mNeon-tagged SFH8 IDR puncta showed a rapid signal recovery (t1/2∼10 s, mobile fraction 40%) and sensitivity to 1,6-hexanediol which may block LLPS ( Figure S4H, I ) (Cuevas-Velazquez et al, 2021; Kroschwald et al, 2017); 1,6-hexanediol led also to the dissolution of SFH8 clusters on the PM but not of filaments ( Figure S4I ).…”
Section: Resultsmentioning
confidence: 99%
“…Precedent for switch-like transitions and dynamics that span a spectrum of timescales has been reported for different IDRs (10,13). Such transitions, especially in the context of tethered systems, are likely to make important contributions to the spatial and temporal control over biochemical reactions where IDRs modulate the effective concentrations of ligands around binding sites or of substrates around active sites of enzymes (31,32,34,57,(101)(102)(103)(104)(105). While our results are presented for IDRs studied as autonomous units, we expect that our findings will be transferable to tethered IDRs, albeit with context-dependent modifications (103,106).…”
Section: Discussionmentioning
confidence: 99%
“…Studies over the past decade have helped quantify relationships (6) that connect sequence-encoded information within IDRs to properties of conformational ensembles such as overall sizes and shapes, the amplitudes of spontaneous conformational fluctuations, and the dynamics of interconverting between distinct conformational states (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). These sequence-ensemble relationships have direct functional consequences that have been uncovered via studies based on biophysical, biochemical, and engineering approaches (5,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Our work, which is focused on physical principles underlying sequence-ensemble relationships of IDRs, is of direct relevance to understanding how IDRs function.…”
mentioning
confidence: 99%